Breastfeeding Self-Efficacy as a Predictor of Exclusive Breastfeeding Success in Mothers of 6–24-Month-Old Toddlers in Rural Indonesia - Khoirunnisa, Marjani; Nurrohmah, Norma; Nurendah, Euis (Poltekkes Kemenkes Tasikmalaya, 2025)
Exclusive breastfeeding coverage in Indonesia is still low (29.5%). The failure of exclusive breastfeeding is influenced by several factors, one of which is self efficacy. Mothers who have a high level of breastfeeding self-efficacy tend to breastfeed until the age of 6-12 months. This study aims to determine the relationship between the level of breastfeeding self-efficacy with the success of exclusive breastfeeding in mothers breastfeeding toddlers aged 6-24 months in Bunijaya Village, Cianjur. This research design is analytic correlation with cross sectional design. Data were collected from 70 respondents who were determined based on total sampling technique. The results showed the majority of mothers had high BSE (92.9%), and most mothers breastfed exclusively (97.1%). There is a relationship between the level of breastfeeding self-efficacy with the success of exclusive breastfeeding (p = 0.004., CI 95%). Based on the results of this study, it is concluded that there is a relationship between the level of breastfeeding self-efficacy with the success of exclusive breastfeeding in breastfeeding mothers of toddlers 6-24 months in Bunijaya Village, Cianjur. It is hoped that this research can be developed by raising other variables besides breastfeeding self-efficacy with the success of exclusive breastfeeding